The transformation of Athens : painted pottery and the creation of classical Greece - Osborne, Robin (Martin classical lectures, 2018)
"Why did soldiers stop fighting, athletes stop competing, and lovers stop having graphic sex in classical Greek art? The scenes depicted on Athenian pottery of the mid-fifth century BC are very different from those of the late sixth century. Did Greek potters have a different world to see-- or did they come to see the world differently? ... Robin Osborne argues that these remarkable changes are the best evidence for the shifting nature of classical Greek culture. Osborne examines the thousands of surviving Athenian red-figure pots painted between 520 and 440 BC and describes the changing depictions of soldiers and athletes, drinking parties and religious occasions, sexual relations, and scenes of daily life. He shows that it was not changes in each activity that determined how the world was shown, but changes in values and aesthetics. By demonstrating that changes in artistic style involve choices about what aspects of the world we decide to represent as well as how to represent them, this book rewrites the history of Greek art. By showing that Greeks came to see the world differently over the span of less than a century, it reassesses the history of classical Greece and of Athenian democracy. And by questioning whether art reflects or produces social and political change, it provokes a fresh examination of the role of images in an ever-evolving world"--Publisher's description